Sorafenib inhibits transforming growth factor β1-Mediated Epithelial-Mesenchymal Transition and apoptosis in mouse hepatocytes - Yue‐Lei Chen; Jing Lv; Xiaolei Ye; Mingyu Sun; Qin Xu; Chenghai Liu; Lihua Min; Huiping Li; Ping Liu; Xiaoyan Ding (2011)
Epithelial-mesenchymal transition (EMT) is a physiological process that has been recognized to occur during the progression of an increasingly large number of human diseases, including liver fibrosis, cirrhosis, and hepatocellular carcinoma. The activation of transforming growth factor β (TGF-β) signaling is considered a critical event during EMT, and efforts have been made to screen small molecules that interfere with the TGF-β signaling pathway during EMT. Here we report the identification of sorafenib, a clinical agent that inhibits TGF-β signaling. When applied to AML12 cells and primary hepatocytes, sorafenib strikingly suppressed TGF-β1-induced EMT and apoptosis. Additionally, sorafenib inhibited TGF-β1-induced signal transducer and activator of transcription 3 phosphorylation. We further present in vitro evidence that sorafenib ameliorates the proapoptotic and profibrotic effects of TGF-β1 in mouse primary hepatocytes, suggesting that this drug exerts a protective effect on hepatocytes and has therapeutic potential for the treatment of liver fibrosis. (HEPATOLOGY 2011;)